RETRACTED: Optimization of streaming processes in ecosystems of transport and logistics services using digital technologies - Gubar M.; Kotova E.; Sivertseva E. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001